Bay of sighs [large type] - Roberts, Nora (Roberts, Nora. Guardians trilogy, 2016)
Mermaid Annika is from the sea, and it is there she must return after her quest to find the three stars that fell from the sky. New to this world, her purity and beauty are nothing less than breathtaking, along with her graceful athleticism, as her five new friends discovered when they retrieved the fire star. Now, through space and time, traveler Sawyer King has brought the guardians to the island of Capri, where the water star is hidden. And as he watches Annika in her element, he finds himself drawn to her joyful spirit. But Sawyer knows that if he allows her into his heart, no compass could ever guide him back to solid ground. And in the darkness, their enemy broods....